The Effect of Utilizing AI Chatbot and Recommendation System on Customer Satisfaction and Retention in Local Marketplace in Bandung - Putra, Johni Eka; Prabowo, Bagus (Westscience Press, 2025)
This study investigates the impact of utilizing AI chatbot technology and recommendation systems on customer satisfaction and retention in a local marketplace in Bandung. A quantitative research design was employed, collecting data from 200 respondents using a structured questionnaire with a 5-point Likert scale. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) to evaluate the relationships between variables. The findings reveal that both AI chatbots and recommendation systems significantly enhance customer satisfaction, with recommendation systems having a stronger influence. Customer satisfaction mediates the relationship between these technologies and customer retention, highlighting its critical role in fostering loyalty. The study provides actionable insights for local marketplaces to leverage AI tools, adapt to customer needs, and gain a competitive advantage. Future research should explore additional factors influencing retention and examine AI adoption in diverse market contexts.